Quincas Laranjeiras (1873-1935) and guitar teaching in Rio de Janeiro: the first between chorões and maidens (Orfeu, 2023)
The purpose of the article is to highlight the decisive activity of Quincas Laranjeiras (1873-1935) as a guitar teacher in socio-cultural groups more linked to popular cultural matrices: chorões, sambistas, regionalists and singers linked to the phonographic industry and the radio, highlighting the relationships with Donga and the ladies and gentlemen of Rio de Janeiro society. In a complementary way, the text touches part of the contexts and dynamics that, at that moment, revolved around the instrument, minimally situating the lives of these characters in time and space. Based on the cross-referencing and analysis of the collected primary sources and the data available in the literature, the results indicate that, throughout the 1920s, Quincas played an important role as a guitar teacher for women practitioners, inserting his pedagogical work within the movement of “resurgence of the national song”.
Keywords: guitar in Rio de Janeiro; guitar teaching; guitar pioneers; female guitarists; “O que é nosso”